1988
DOI: 10.1136/hrt.60.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiocentesis and systemic cytotoxic chemotherapy in the management of cardiac tamponade secondary to disseminated breast carcinoma.

Abstract: SUMMARY Three patients with cardiac tamponade secondary to disseminated breast carcinoma were treated by pericardiocentesis followed by systemic cytotoxic chemotherapy. This approach controlled pericardial effusion in all the patients and extended their survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Thus, the echocardiographic finding of a mass in the left atrium accompanied by fever was not enough to lead clinicians to favor a working diagnosis of myxoma. While breast cancer has been reported to cause malignant pericardial effusion, 7 true intracavitary metastases (as suspected in this case) are rare. Tumor encasement of the heart in a case of breast cancer has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the echocardiographic finding of a mass in the left atrium accompanied by fever was not enough to lead clinicians to favor a working diagnosis of myxoma. While breast cancer has been reported to cause malignant pericardial effusion, 7 true intracavitary metastases (as suspected in this case) are rare. Tumor encasement of the heart in a case of breast cancer has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The pericardial fluid was malignant in 97.4% (n=42) of the cases and benign in one patient. From the studies that reported the time to tamponade [2,3,7,8,[10][11][12][13][14][15][16]18], the median time to the occurrences of cardiac tamponade after the first cancer treatment was 26 months (0-156). There was no evidence of metastases to other extra-pericardial secondary sites in three of the included studies [11,13,15].…”
Section: Pathologic Characteristics Of Study Participantsmentioning
confidence: 99%
“…Fifteen studies reported survival time [1][2][3][4]7,[9][10][11][12][13][14][15][16][17][18]. The median survival time after diagnosis of tamponade was 13 months (0.13-57) (Table 4).…”
Section: Table 4: Intervention and Outcomes Of Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without any additional treatment, the rate of recurrence is high (up to 40%) and by extending the drainage for several days, the rate of recurrence is reduced [66] . Systemic CT without further local interventions has been reported to be effective in lymphomas and in some cases of solid tumors (mostly breast and ovarian) [67][68][69][70][71][72] .…”
Section: Percutaneous Drainagementioning
confidence: 99%